Procalcitonin Impairs Liver Cell Viability and Function In Vitro: A Potential New Mechanism of Liver Dysfunction and Failure during Sepsis?. (1st February 2017) - Sauer, Martin; Doß, Sandra; Ehler, Johannes; Mencke, Thomas; Wagner, Nana-Maria
Abstract : Purpose . Liver dysfunction and failure are severe complications of sepsis and result in poor outcome and increased mortality. The underlying pathologic mechanisms of hepatocyte dysfunction and necrosis during sepsis are only incompletely understood. Here, we investigated whether procalcitonin, a biomarker of sepsis, modulates liver cell function and viability. Materials and Methods . Employing a previously characterized and patented biosensor system evaluating hepatocyte toxicity in vitro, human hepatocellular carcinoma cells (HepG2/C3A) were exposed to 0.01–50 ng/mL procalcitonin for 2 × 72 h and evaluated for proliferation, necrosis, metabolic activity, cellular integrity, microalbumin synthesis, and detoxification capacity. Acetaminophen served as positive control. For further standardization, procalcitonin effects were confirmed in a cellular toxicology assay panel employing L929 fibroblasts. Data were analyzed using ANOVA/Tukey's test. Results . Already at concentrations as low as 0.25 ng/mL, procalcitonin induced HepG2/C3A necrosis (P < 0.05 ) and reduced metabolic activity, cellular integrity, synthesis, and detoxification capacity (all P < 0.001 ). Comparable effects were obtained employing L929 fibroblasts. Conclusion . We provide evidence for procalcitonin to directly impair function and viability of human hepatocytes and exert general cytotoxicity in vitro . Therapeutical targeting of procalcitonin could thus display a novel approach to reduce incidence of liver dysfunction and failure during sepsis and lower morbidity and mortality of septic patients.